Упростите выражение 5а - (8а - 6) 6а - b + (3b - 9a) 12 - 5 (4p - 3) Буду очень...

0 голосов
16 просмотров

Упростите выражение
5а - (8а - 6)
6а - b + (3b - 9a)
12 - 5 (4p - 3)


Буду очень благодарна, заранее спасибо!


Алгебра (17 баллов) | 16 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

5a - (8a - 6) = 5a - 8a + 6 = 6 - 3a = 3(2 - a)
6a - b + (3b - 9a) = 6a - b + 3b - 9a = 2b - 3a
12 - 5(4p - 3) = 12 - 20p + 15 = 27 - 20p

(271k баллов)
0 голосов

1)5а-8а+6=-3а+6=3(2-а)
2)6а-б+3б-9а=-3а+2б=2б-3а
3)12-20р+15=27-20р

(16.0k баллов)